Murine gammaherpesvirus-68 (MHV-68) is not horizontally transmitted amongst laboratory mice by cage contact. (October 2015) - Aligo, Jason; Brosnan, Kerry; Walker, Mindi; Emmell, Eva; Mikkelsen, S. Rochelle; Burleson, Gary R.; Burleson, Florence G.; Volk, Amy; Weinstock, Daniel
Abstract Murine gammaherpesvirus-68 (MHV-68), a natural pathogen of mice, is being evaluated as a model of Epstein Barr Virus (EBV) infection for use in investigation of the effects of immunomodulatory therapy on herpesvirus pathogenesis in humans. Immunosuppressive agents are used for treatment of a variety of autoimmune diseases as well as for prevention of tissue rejection after organ transplantation and can result in recrudescence of latent herpesvirus infections. Prior to examination of MHV-68 as a suitable model for EBV, better characterization of the MHV-68 model was desirable. Characterization of the MHV-68 model involved development of assays for detecting virus and for demonstration of safety when present in murine colonies. Limited information is available in the literature regarding MHV-68 transmission, although recent reports indicate the virus is not horizontally spread in research facilities. To further determine transmission potential, immunocompetent and immunodeficient mice were infected with MHV-68 and co-habitated with naïve animals. Molecular pathology assays were developed to characterize the MHV-68 model and to determine viral transmission. Horizontal transmission of virus was not observed from infected animals to naïve cagemates after fluorescence microscopy assays and quantitative PCR (qPCR). Serologic analysis complemented these studies and was used as a method of monitoring infection amongst murine colonies. Overall, these findings demonstrate that MHV-68 infection can be controlled and monitored in murine research facilities, and the potential for unintentional infection is low.